Bifunctional electrochromic-energy storage materials with enhanced performance obtained by hybridizing TiO2 nanowires with POMs. (1st September 2020) - Qu, Xiaoshu; Fu, Yu; Ma, Chao; Yang, Yanyan; Shi, Dan; Chu, Dongxue; Yu, Xiaoyang
Abstract : A bifunctional electrochromic-energy storage film with enhanced performance is designed and fabricated by hybridizing TiO2 nanowires with POMs. Abstract : Multifunctional electrode materials have been widely studied in recent years, owing to their various excellent performances. Herein, we report a nanocomposite film based on Dawson-type monolacunary polyoxotungtate K10 P2 W17 O61 and TiO2 nanowires fabricated via hydrothermal and layer-by-layer self-assembly combination methods, in which the bifunctional combination of electrochromism energy storage was successfully realized. Compared to individual K10 P2 W17 O61 thin films, the nanocomposite films showed outstanding electrochromic properties of high coloration efficiency (150.34 cm 2 C −1 at 600 nm) and cyclic stability, and the volumetric capacitance of the composite film reaches 172.3 F cm −3 with a working voltage window of 1.77 V. The greater electrochemical properties could be due to the unique 3D structure of the TiO2 NW arrays, which provides a larger electrolyte contact area and a shorter ion diffusion pathway available for the redox reactions. Our study provides a new route to design bifunctional electrode materials with enhanced electrochromism and energy storage functions, making polyoxometalate-based electrode materials more attractive for practical applications.